Culling and Replacement Rate in the Beef Cow Herd - Matt Hersom; Todd Thrift; Joel Yelich (EDIS)
Culling decisions are important to maintain the productivity and profitability of the beef cow herd. Culling of cows from the herd eliminates poorly performing cows, inferior genetics, and cows with quality defects that would limit short- and long-term productivity. This 4-page fact sheet discusses reasons to cull as well as replacement of culled cows. Written by Matt Hersom, Todd Thrift, and Joel Yelich, and published by the UF Department of Animal Sciences, December 2015.